Leveraging Entrepreneurial Bricolage and Innovation Performance among Manufacturing SMEs in Malaysia Under a Resource Constrained Environment - Abdul-Halim, Hasliza; Andalib, Tarnima Warda; Ahmad, Noor Hazlina; Ramayah, Thurasamy (ExcelingTech, 2020)
SMEs are essential to Malaysian economy as they became one of important economic driver in the nation. In order for Malaysia to reach high income nation, SMEs have to be more resilient toward business uncertainty. In order to survive in globalize market, SMEs have to embrace innovation to maintain their competitive edge. However, investing in innovation comes with cost attached and due to their sizes, SMEs also encounter various external and internal resource constraints. Under logical assumption, these constrains may hinder firms to invest in innovation however, that is not the case as some SMEs are able to strive in resource constrained environment. In order to understand the underlying factors that contribute to this scenario, a research framework has been proposed. This study has adopted the concept of bricolage to explain innovation performance among manufacturing SMEs in Malaysia that operate under resource constrained environment. By adopting quantitative approach, this study has collected 217 sets of data from the Federation of Malaysian Manufactures (FMM) Directory for 2016. The response rate of the survey is at 43.4% and the data is analysed through PLS-SEM. After the establishment of construct’s validity and reliability, the study has confirmed a significant positive relationship between entrepreneurial bricolage and innovation performance. The study has also found that constraints in financial and human resources have a positive influence on bricolage behaviour, although the explanatory power for this relationship is not strong. Nevertheless, this study has provided an answer to scenario where some firms may strive even in resource constrained environment. This study is original and valuable with respect to data and context. The findings of this study may play a substantial role in the economic stability of Malaysia by enriching the SMEs sector.